2022
DOI: 10.1039/d2fo02672d
|View full text |Cite
|
Sign up to set email alerts
|

DHA-enriched phosphatidylcholine from Clupea harengus roes regulates the gut–liver axis to ameliorate high-fat diet-induced non-alcoholic fatty liver disease

Abstract: In this study, the protective effect of DHA-enriched phosphatidylcholine (DHA-PC) from Clupea harengus roes against high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD) was investigated. Our results indicated that DHA-PC...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Moreover, we found the abundance of Lachnospiraceae_NK4A136_group was sharply increased after FMT. Lachnospiraceae_NK4A136_group as a butyrate-producing bacterium could maintain intestinal barrier integrity and protect against obesity [44]. These results showed that SB positively regulated the gut microbiota composition and improved bacteria diversity.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, we found the abundance of Lachnospiraceae_NK4A136_group was sharply increased after FMT. Lachnospiraceae_NK4A136_group as a butyrate-producing bacterium could maintain intestinal barrier integrity and protect against obesity [44]. These results showed that SB positively regulated the gut microbiota composition and improved bacteria diversity.…”
Section: Discussionmentioning
confidence: 76%
“…Colidextribacter , an HFD-dependent species, could be promoted by a high-fat and high-cholesterol diet [ 47 , 48 ]. A higher abundance of Clostridia_UCG-014 induced by a HFD was also observed [ 49 ]. However, it was found to have a negative association with serum lipid levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Lachnospiraceae NK4A136 group is considered a probiotic strain. Its relative abundance is reduced in DSS-induced colitis [ 57 , 58 , 59 ], in acetic acid-induced colitis [ 60 ], and in lipopolysaccharide (LPS)-induced intestinal mucosal injury [ 61 ], as well as in obese [ 62 , 63 , 64 , 65 ] and peanut-allergic mice [ 66 ]. A2 strain also belongs to the Lachnospiraceae family, but is less known.…”
Section: Discussionmentioning
confidence: 99%